Validation of the TSH IRMA Kit for Determination of the TSH Levels in Human Blood Serum - Gina Mondrida; Sutari Sutari; Triningsih Triningsih; Sri Setyowati; V. Yulianti S; Wening Lestari; Agus Ariyanto; Puji Widayati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2018)
TSH IRMA kit is a kit used for the determination of TSH (Thyroid Stimulating Hormone) levels in human blood serum. Thyroid hormone is a hormone that our bodies need for growth of the brain, bone and other tissues and regulate the metabolism in the body. TSH normal range for adult is in the range of 0.4-4.5 mIU/L, whereas for baby is about 3.0-18.0 mIU/L. Thyroid would affect the quality of optimal growth of children if disturbed. Therefore, TSH assay in the blood needs to be determined to know whether the function of the thyroid gland works normally or not. Detection of TSH in blood can be performed by Immunoradiometricassay (IRMA) method. IRMA method is one of the immunoassay techniques based on immunological reactions (antigen-antibody binding) using radionuclide 125I as a tracer, that sample in small quantity can be detected. IRMA method was developed locally by replacing TSH IRMA kit which is costly since imported from commercial companies. Center for Radioisotope and Radiopharmaceutical Technology (PTRR) BATAN has successfully developed the TSH IRMA kit that can be used to determine the levels of TSH in human blood. TSH IRMA kit must be validated to know the limit of detection, sensitivity, accuracy, precision and the assay parameters, such as Non-Specific Binding (NSB) and Maximum Binding (MB). Validation of TSH IRMA kit had been carried out resulting in the limit of detection of 0.115 ng/mL, accuracy with a recovery of 93.6-108.0 %, intra-assay precision (% CV) QC L = 1.9848, QC M = 3.6360 % and QC H = 2.2085 % while the inter-assay precision (% CV) QC L = 11.0055, QC M = 5.6768 % and QC H = 5.4181 %. It was concluded that this TSH IRMA kit showed good performance based on the % NSB and % B/T of 0.68 and 34.64 %, respectively.